2005
DOI: 10.1093/tropej/fmi015
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Childhood Helicobacter Pylori Infection and Iron Deficiency Anemia?

Abstract: An association between Helicobacter pylori infection and iron deficiency anemia has been reported in children, and it has been proposed that H. pylori infection needs to be eradicated to treat absolutely iron deficiency anemia (IDA). We investigated whether there was any correlation between H. pylori infection and iron deficiency (ID) and IDA in children, and whether the eradication of H. pylori infection without iron treatment would lead to the resolution of ID. Hemoglobin and ferritin levels, H. pylori stool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 10 publications
5
55
0
2
Order By: Relevance
“…Lower socioeconomic status, crowded families and sharing of common living areas with compromised hygiene can also lead to increase the dissemination of H. pylori [36] . In our study, H. pylori positive cases revealed a significant difference in the incidence of anemia (Table 2) and these results are in accordance with another previous study done by Kurekci et al [37] . Development of anemia during H. pylori infection could be originated from poor absorption of iron due to low gastric acid secretion and/or poor dietary intake and utilization of iron by the bacterial flora [29] .…”
Section: Patientssupporting
confidence: 93%
“…Lower socioeconomic status, crowded families and sharing of common living areas with compromised hygiene can also lead to increase the dissemination of H. pylori [36] . In our study, H. pylori positive cases revealed a significant difference in the incidence of anemia (Table 2) and these results are in accordance with another previous study done by Kurekci et al [37] . Development of anemia during H. pylori infection could be originated from poor absorption of iron due to low gastric acid secretion and/or poor dietary intake and utilization of iron by the bacterial flora [29] .…”
Section: Patientssupporting
confidence: 93%
“…Studies have shown that H. pylori eradication may be useful in treating the iron deficiency and iron deficiency anaemia without iron replacement [19]. Similarly, it has been reported that H. pylori eradication may be useful in treating vitamin B12, vitamin A and vitamin E deficiencies without replacing these vitamins [11].…”
Section: Discussionmentioning
confidence: 99%
“…16,30 Comparison between HP positive cases and HP negative cases revealed a statistically significant difference in the incidence of iron deficiency anemia (p=0.025). 41,42 The postulated mechanisms for IDA in H. pylori infection include, poor absorption of iron due to low gastric acid secretion, poor dietary intake and utilization of iron by the bacteria itself. 26 A meta-analysis of observational studies suggests an association between H. pylori and IDA.…”
Section: It Is Not Yet Clear Whether the Difference In Anthropometrymentioning
confidence: 99%